Maintenance olaparib monotherapy in patients with platinum-sensitive relapsed ovarian cancer without a germline BRCA1 and/or BRCA2 mutation: Final overall survival results from the OPINION trial - Poveda, Andrés; Lheureux, Stéphanie; Colombo, Nicoletta; Cibula, David; Elstrand, Mari; Weberpals, Johanne; Bjurberg, Maria; Oaknin, Ana; Sikorska, Magdalena; González-Martín, Antonio; Madry, Radoslaw; Rubio Pérez, María Jesus; et al. (Gynecologic oncology, 2025)
OBJECTIVE: Maintenance olaparib demonstrated clinical activity for progression-free survival in patients without a germline BRCA1 and/or BRCA2 mutation (non-gBRCAm) who had platinum-sensitive relapsed ovarian cancer in the phase IIIb, open-label, single-arm, non-comparator, international OPINION trial (NCT03402841). We report final overall survival (OS; secondary endpoint), prespecified secondary endpoint updates and ad hoc OS analysis by homologous recombination deficiency (HRD) and somatic BRCAm (sBRCAm) status. METHODS: Patients with non-gBRCAm platinum-sensitive relapsed ovarian cancer, ≥2 prior lines of platinum-based chemotherapy, and in response following their last platinum-based chemotherapy received 300 mg olaparib tablets twice daily until disease progression or unacceptable toxicity. RESULTS: 279 patients were enrolled and treated. With a median follow-up in patients censored for OS of 33.1 months (data cut-off September 17, 2021), median OS was 32.7 months (95 % CI 29.5-35.3); the 24-month OS rate was 65.8 %. In ad hoc subgroup analyses, OS rates tended to be higher in patients with HRD-positive tumors; 24-month OS rates were 81.5 %, 74.2 %, 72.0 % and 55.8 % in the sBRCAm, HRD-positive including sBRCAm, HRD-positive excluding sBRCAm, and HRD-negative subgroups, respectively. Grade ≥ 3 treatment-emergent adverse events were reported in 82 patients (29.4 %), most commonly anemia (13.6 %). Overall, two cases of myelodysplastic syndrome were reported (no new cases since the primary analysis). CONCLUSION: These data provide additional evidence of olaparib as maintenance therapy in patients with non-gBRCAm platinum-sensitive relapsed ovarian cancer, with longer OS observed in those with HRD-positive tumors. The safety profile was consistent with the primary analysis and known safety profile of olaparib, with no new safety findings.
Keywords: ftalaziny; udržovací chemoterapie; protein BRCA2; protein BRCA1; epiteliální ovariální karcinom; Aged; Ovarian cancer; Maintenance; Piperazines; Carcinoma, Ovarian Epithelial; lidé středního věku; senioři; Progression-Free Survival; Maintenance Chemotherapy; BRCA1 Protein; lidé; piperaziny; Adult; nádory vaječníků; Middle Aged; lokální recidiva nádoru; dospělí; zárodečné mutace; Neoplasm Recurrence, Local; PARP inhibitory; Ovarian Neoplasms; Female; Poly(ADP-ribose) Polymerase Inhibitors; ženské pohlaví; doba přežití bez progrese choroby; Humans; Olaparib; Phthalazines; Germ-Line Mutation; BRCA; BRCA2 Protein